Effect of Breastfeeding Education on Mother’s Knowledge and Infant Weight Gain - Said, Norimah; Mazlan, Marlina; Shahruddin, Rashidah (International Journal of Engineering and Technology, 2018)
Breastfeeding education should be delivered by a person who is qualified and expertise in lactation management. This study is conducted to evaluate the effects of breastfeeding education on mothers’ knowledge and infantsâ€™ weight gain. The mothers received individual and group counselling education interventions. The intervention resulted in a significant difference in the level of knowledge regarding post breastfeeding education between groups (p< 0.001). However, the infantsâ€™ weight patterns showed an increase in total of 489 grams for the control group and 356 grams for the intervention group by week four. Support from nurses is vital for the successful assistance of mothers in breastfeeding to empower them and boost their confidence. Â Â